Implementation Of The Jigsaw Learning Model To Improve Student Learning Outcomes In Akidah Akhlak For Grade VI At MI PSM Gedoro - Dewi Nur Allipah; Anggun Saskiya; Miftahul Halima (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
Akidah Akhlak as a subject in Islamic education at MI PSM Gedoro often faces challenges in student engagement due to its perceived monotony. In this study, the Jigsaw learning model is applied to address this issue, with the aim of clarifying the teacher's presentation of the material, addressing active student participation, and overcoming space limitations to make learning more effective. In this model, the teacher provides each student with the opportunity to study a portion of the material so that they become experts in their respective areas. This expertise is then taught to their peers in other groups. Peers in other groups also study different parts of the material and become experts in their areas. The interaction that occurs is a sharing pattern of learning, where each student gains high confidence due to having unique expertise needed by others. Each student will feel interdependent and reliant on others. The choice of the Jigsaw learning model for the Akidah Akhlak subject is intentionally made to engage students actively during the learning process, review previously learned material, gain a detailed understanding of the content, and build good cooperation among peers. Classroom Action Research (CAR) is used as the research methodology. The results of the first cycle show that 34.78% of students scored above 75, which increased to 82.61% in the second cycle. This indicates that the Jigsaw learning model effectively enhances student engagement and learning result.